Chapter The forgotten nautical astronomical instruments - Benincasa, Fabrizio (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
Astrology and meteorology have always had great importance for agriculture and navigation. They are described some measuring and forecasting instruments which, in the past, had a moderate success to navigate the Mediterranean, but they were forgotten because they were supplanted by other more reliable instruments in oceans. We refer to: parapegma, (made when meteorology was still a particular aspect of astrology); a calculator for determining the position of stars; instruments to establish position of a ship with respect to the Sun or the North Pole and to determine ships direction and speed